The Study Of Agar Binder And Super P Additive In Porous Zinc Anode For Zinc-Air Batteries - Masri, Mohamad Najmi (2013)
A zinc-air (Zn-air) battery was fabricated using porous Zn anode, an air cathode, and 6 M KOH-sago gel electrolyte. The porous Zn anode was prepared by mixing Zn powder and agar binder at different concentrations to achieve the desired conductivity and physical properties. Agar is an abundant natural polymer that does not require tedious and costly processing or preparation. Agar is also a gel-forming environmental friendly material. Meanwhile, the presence of KOH causes the growth of ZnO needle structures to cover the Zn-active material. Zn-agar binder without KOH produced the highest discharge capacity of 505 mAhg1. By contrast, the addition of KOH reduced the discharge capacity. The introduction of Super P improved the electrochemical performance of the batteries. The advantages of using Super P in batteries include high purity, large area, and highly structured body. The use of Super P additive in porous Zn anode enhanced the Zn-air battery discharge capacity because of the efficient and better voltage stability obtained from such an anode. The specific discharge capacity and power density of Zn anode with 2 wt% Super P were 776 mAhg1 and 20 mWcm2, respectively. Morphological images and structural properties were also analyzed to support these observations. Super P acted as a bridge in the Zn powders and improved the electrochemical performance of the Zn-air batteries.